2019
DOI: 10.1016/j.paid.2018.07.039
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation into the relationship between empathy, autistic like traits and emotion recognition

Abstract: Kris (2019) A preliminary investigation into the relationship between empathy, autistic like traits and emotion recognition. Personality and Individual Differences, 137. pp. 12-16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The stimuli in the study were comparable to those in interventions and assessments of emotion recognition, used in clinical and educational settings (e.g., Murray et al, 2018). Hypotheses H1 and H4, which states that non-autistic people and people with lower autistic traits will more accurately recognise emotions than autistic people and people with higher autistic traits, were supported; findings which are consistent with past research (see Martin et al, 2019;Uljarevic & Hamilton, 2013). Decoding emotions is central to social interaction (Harms et al, 2010), therefore, the results suggest that autistic adults may be at a disadvantage in social relationships.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The stimuli in the study were comparable to those in interventions and assessments of emotion recognition, used in clinical and educational settings (e.g., Murray et al, 2018). Hypotheses H1 and H4, which states that non-autistic people and people with lower autistic traits will more accurately recognise emotions than autistic people and people with higher autistic traits, were supported; findings which are consistent with past research (see Martin et al, 2019;Uljarevic & Hamilton, 2013). Decoding emotions is central to social interaction (Harms et al, 2010), therefore, the results suggest that autistic adults may be at a disadvantage in social relationships.…”
Section: Discussionsupporting
confidence: 86%
“…A further review (Black et al, 2017) concluded that the cognitive processes employed by autistic people are atypical, but patterns across studies are inconsistent. These results extend to the non‐autistic population, with autistic traits predicting emotion recognition ability; people with higher autistic traits perform more poorly overall (e.g., Martin et al, 2019). Other studies, however, show that autistic adults (e.g., Adolphs et al, 2001) and children (e.g., Shanok et al, 2019) perform comparably to non‐autistic peers.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…The assessment stimuli also vary in the amount of contextual information available. This is important because research has indicated that the amount and type of contextual information can impact differentially on the accuracy of ER in individuals with and without a developmental disability (Barrett et al, 2011;McKenzie et al, 2001;Martin et al, 2019;Murray et al, 2019;Scotland et al, 2016;Teh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%